Retensi Ekstrak Karoten pada Olahan Mie Wortel (Daucus carrota L.): Retention of Carotene Extract on Carrot (Daucus carrota L.) Noodles - Putri Wahyuni; Ni Ketut Sumarni; Prismawiryanti; Jaya Hardi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Carotene extract from carrots (Daucus carrota L.) can improve the quality of processed noodles. Determining of carotene retention in processed carrot noodles during the storage period that has been done aims to know the reaction kinetics and shelf life of the noodles. Carrot noodles were stored for 8 weeks at room temperature and analyzed its carotene content by using a UV-Vis spectrophotometer every 7 days. The result showed that the retention of carrot noodles during storage of 0, 1, 2, 3, 4, 5, 6, 7, and 8 weeks was 53.64%, 53.19%, 52.49%, 51.68%, 51.07%, 46.30%, 45.96, 45.88, and 44.93%, respectively. The retention kinetics of carrot noodles during storage followed a zero-order reaction and had a shelf life of up to 30 weeks, 4 days, 4 hours. Keywords: carrot noodles, retention, self life